Constructing and standardizing Effective Administration Scale for Iraqi Basketball Federation from Employees' Point of View - Omer Saad Huait; Huda Hameed (College of Physical Education and Sport Sciences, 2021)
The study aimed at constructing and standardizing effective administration for the Iraqi basketball federation from employees' point of view. The researchers used the descriptive method on (424) administrative bureau members, (54) sub federations members as well as (10) certified national league coaches making a total of (547). The pilot study and the data were collected to conclude (5) standard levels of the scale. Finally, the researchers recommended using these scores and levels for measurement.